2021
DOI: 10.1155/2021/8885290
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cell Viability and Chemical Composition of Six Latest Generation Orthodontic Wires

Abstract: Orthodontic wires are made of alloys containing different metals, including nickel. It is important to evaluate their biocompatibility prior to use, owing to their long-term use in patients. This in vitro study compared the cytotoxicity and chemical composition of six latest orthodontic wires: Fantasia®, Tanzo®, FLI®, NT3®, DuoForce®, and Gummetal®. The before-use group consisted of wires that were not used in the mouth, and the after-use group consisted of wires that were used in the mouth for two months. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Katić Višnja et al [ 170 ] and Milena Carolina de Amorim et al [ 184 ] both suggested that rhodium coating reduces the corrosion resistance and electrochemical resistance of NiTi archwires in artificial saliva, making them more susceptible to localized pitting corrosion on the surface. Lina M. Escobar et al [ 185 ] described rhodium-plated NiTi archwire as having a significantly rougher surface and many scratches on its surface after testing. This indicates that the wear resistance of rhodium plating is also less than satisfactory.…”
Section: Corrosion-resistant Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Katić Višnja et al [ 170 ] and Milena Carolina de Amorim et al [ 184 ] both suggested that rhodium coating reduces the corrosion resistance and electrochemical resistance of NiTi archwires in artificial saliva, making them more susceptible to localized pitting corrosion on the surface. Lina M. Escobar et al [ 185 ] described rhodium-plated NiTi archwire as having a significantly rougher surface and many scratches on its surface after testing. This indicates that the wear resistance of rhodium plating is also less than satisfactory.…”
Section: Corrosion-resistant Coatingsmentioning
confidence: 99%
“…The corrosion rate of a PTFE-coated NiTi archwire was 10 times lower than that of uncoated NiTi substrates [ 192 ]. However, PTFE may exhibit slight cytotoxicity to fibroblasts—approximately 36% [ 185 ]. Therefore, careful consideration is needed when choosing this material.…”
Section: Corrosion-resistant Coatingsmentioning
confidence: 99%
“…Nowadays, fibroblast cell lines (periodontal ligament, gingival, or dermal [ 9 , 10 , 11 , 12 , 13 , 14 ]), gastrointestinal tract cell lines [ 15 , 16 ], and sometimes yeast [ 17 , 18 ] are most commonly used for testing. Research has focused mainly on NiTi or stainless (arch)wires [ 2 , 13 , 19 , 20 ], brackets [ 2 , 12 , 14 ], and bands [ 2 , 9 , 10 , 16 , 21 ].…”
Section: Introductionmentioning
confidence: 99%